Penyesuaian Diri Anak Korban Perceraian di Lingkungan Sosial Sekolah - M. Harwansyah Putra; Aika Azzura; Halimah Halimah; Rafiqah Umry Siregar,; Sri Rezky (Jurnal Dirosah Islamiyah, 2023)
The purpose of this study was to find out how the adjustment of children of divorce victims at the Vocational High School (SMK) Broadcasting Bina Creative (BBC) Medan, this study used a quantitative survey using a questionnaire on students. The data analysis technique used is descriptive quantitative. The research sample was 5 students from the BBC (Broadcasting Bina Creative) Medan Vocational High School. The results of this study explain that the self-adjustment of students is in the less than 80% criterion, namely the sufficient criterion. Keywords: Divorce victim, Child adjustment